2010
DOI: 10.3329/jhpn.v28i2.4886
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profiles and <i>trans</i> Fatty Acids in Serum Phospholipids of Semi-nomadic Fulani in Northern Nigeria

Abstract: The Fulani are semi-nomadic pastoralists of West Africa whose diet, culture, and economy are centred on cattle. Previous studies have shown that the Fulani of northern Nigeria derive 50% of their total calories from fat and 30% of their calories from milk, cheese, yogurt, and butter oil that contain significant amounts of trans fatty acids (TFAs), primarily vaccenic acid, which raise total serum cholesterol and low-density lipoproteincholesterol (LDL-C), and lower high-density lipoprotein-cholesterol (HDL-C). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(36 reference statements)
0
4
1
Order By: Relevance
“…In Abdelmagid et al [ 6 ] when males and females were compared PAO, ALA, and DHA were also all significantly greater except, males had greater concentrations of ALA. In terms of percent composition, Glew et al [ 30 ] found no significant difference between males and females in any of the ten FA highlighted in our study. Independent of dietary intake, females have exhibited a greater genetic capacity to endogenously produce omega-3 PUFA [ 64 ].…”
Section: Discussioncontrasting
confidence: 68%
See 4 more Smart Citations
“…In Abdelmagid et al [ 6 ] when males and females were compared PAO, ALA, and DHA were also all significantly greater except, males had greater concentrations of ALA. In terms of percent composition, Glew et al [ 30 ] found no significant difference between males and females in any of the ten FA highlighted in our study. Independent of dietary intake, females have exhibited a greater genetic capacity to endogenously produce omega-3 PUFA [ 64 ].…”
Section: Discussioncontrasting
confidence: 68%
“…Furthermore, relative percent can be derived from absolute concentrations, but the same is not possible in reverse as the values of the internal standard used in the study are needed to calculate absolute concentration [ 5 ]. As our study included over sixty FA, whereas Bradbury et al [ 9 ] and Glew et al [ 30 ] only included up to twenty-six, it is difficult to accurately compare our reported values even in terms of percent composition. Thus, the use of absolute concentrations is recommended for future studies profiling FA reference ranges to improve comparability and generalizability of results.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations